Gram‐Scale mRNA Production Using a 250‐mL Single‐Use Bioreactor. Issue 12 (10th October 2022) - Skok, Janja; Megušar, Polona; Vodopivec, Tina; Pregeljc, Domen; Mencin, Nina; Korenč, Matevž; Krušič, Andreja; Celjar, Anže Martinčič; Pavlin, Nejc; Krušič, Jana; Mueller, Matthias; McHugh, Kevin; et al.
Abstract: The COVID‐19 pandemic triggered an unprecedented surge in development of mRNA‐based vaccines. Despite the need to increase process productivity and thus decrease the cost of mRNA vaccines, limited scientific literature is available on strategies to increase the yield of in vitro transcription (IVT) reaction, the unit operation with highest cost of goods, which has traditionally been performed as a batch reaction. Single‐use bioreactors are traditionally used for cell‐based production of biopharmaceuticals, but some core functionalities, such as controlled and automated feed addition, are potentially useful for cell‐free mRNA processes. We report the production of 2 g mRNA in an Ambr® 250 Modular bioreactor system with a starting volume of 100 mL, reaching a maximum mRNA concentration of 12 g L −1 by a fed‐batch IVT approach, and demonstrate the feasibility of continuous fed‐batch production, paving the way towards continuous manufacturing of mRNA. Abstract : mRNA is typically produced in a batch IVT reaction. Single‐use bioreactors offer controlled, automated feed addition. We report a fed‐batch production of mRNA in an Ambr® 250 Modular bioreactor, reaching a mRNA concentration of 12 g L −1 by a fed‐batch IVT approach, and demonstrate the feasibility of continuous fed‐batch production of mRNA at gram scale.